Activity and participation experiences of people with disabilities in Ethiopia - Terry Krupa; Rosemary Lysagh; Yetnayet S. Yehuala; Heather M. Aldersey; Molalign B. Adugna; Dorothy Kessler; Beata Batorowicz; Jasmine Montagnese; Klodiana Kolomitro (African Journal of Disability, 2022)
Background: Ethiopia, as a State Party to the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD), has committed to upholding the rights of people with disabilities in Ethiopia. There is little evidence, however, reflecting the impact of this commitment on the lived experiences of people with disabilities in Ethiopia.